Molecular genetic basis of the primary emotions in young adults: an exploratory analysis of genetic polymorphisms across dopamine, serotonin, oxytocin, endogenous opioid, and neurotrophic factor pathways - Glavač, Timotej; Barbo, Maruša; Ravnik-Glavač, Metka; Zupančič, Maja; Dolžan, Vita (Frontiers in Pharmacology, 2025)
IntroductionAdvances in affective neuroscience have unraveled the neurobiological underpinnings of primary emotions, making them suitable candidates for molecular genetic research. The aim of this study was to perform an exploratory molecular genetic association analysis of primary emotions in humans.MethodsA total of 333 young adults (Mage = 21.96 years, SD = 2.48; 56.8% female) participated in this study. Participants were recruited predominantly from a local university using a community sampling procedure. Data were collected via an online questionnaire (1ka.si) which primarily included a validated measure of the primary emotions, specifically the (Affective Neuroscience Personality Scales – Brief) and demographic information. Participants provided informed consent prior to completing the survey, and responses were anonymized. Following the survey, participants provided buccal swabs and their DNA was genotyped for 14 single nucleotide polymorphisms across five genes relevant to KEGG pathways, including dopamine (COMT rs4680, rs165815), serotonin (TPH2 rs1843809, rs4290270, rs7305115, rs4570625), oxytocin (OXTR rs53576, rs968389, rs2268498), endogenous opioid (OPRM1 rs1799971, rs677830), and neurotrophic factor (BDNF rs6265, rs28722151, rs11030101).ResultsOur findings revealed several significant and nominally significant associations between genetic polymorphisms and primary emotions which showed a clear sex-specific pattern. In males, associations were found with the COMT and TPH2 polymorphisms. Specifically, COMT rs4680 was associated with ANGER and SADNESS, TPH2 rs1843809 with PLAY, rs7305115 with CARE, and rs4570625 with CARE and SADNESS. In females, the three BDNF polymorphisms were differentially associated with FEAR, SADNESS (rs28722151 and rs11030101), and ANGER (rs6265). In the total sample, interaction effects were also found between the two OPRM1 polymorphisms (rs1799971 and rs677830) with SADNESS and SEEKING.DiscussionOverall, the present study identified several novel candidate genes which might be related to primary emotions in a sample of young adults. Although our findings should be considered preliminary, they may have important implications for personality research as well as clinical practice.